2017
DOI: 10.3389/fpsyg.2017.01395
|View full text |Cite
|
Sign up to set email alerts
|

The Reporting Quality of Systematic Reviews and Meta-Analyses in Industrial and Organizational Psychology: A Systematic Review

Abstract: Objective: The goal of this systematic review was to examine the reporting quality of the method section of quantitative systematic reviews and meta-analyses from 2009 to 2016 in the field of industrial and organizational psychology with the help of the Meta-Analysis Reporting Standards (MARS), and to update previous research, such as the study of Aytug et al. (2012) and Dieckmann et al. (2009).Methods: A systematic search for quantitative systematic reviews and meta-analyses was conducted in the top 10 journa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 27 publications
0
32
0
Order By: Relevance
“…Many researchers dedicate efforts to the field of WOP, and several works have studied the relationships between individuals and organizations. Although many studies have reviewed WOP ( Billings and Wroten, 1978 ; Cascio, 1995 ; Bond and Smith, 1996 ; Brutus et al, 2010 ; Gelfand et al, 2017 ; Schalken and Rietbergen, 2017 ; Bal et al, 2019 ) and discussed several characteristics and their impacts for individuals and organizations, no work presents a complete background of the field of study. This review is the first bibliometric performance and network analysis (BPNA) performed in the field of WOP.…”
Section: Introductionmentioning
confidence: 99%
“…Many researchers dedicate efforts to the field of WOP, and several works have studied the relationships between individuals and organizations. Although many studies have reviewed WOP ( Billings and Wroten, 1978 ; Cascio, 1995 ; Bond and Smith, 1996 ; Brutus et al, 2010 ; Gelfand et al, 2017 ; Schalken and Rietbergen, 2017 ; Bal et al, 2019 ) and discussed several characteristics and their impacts for individuals and organizations, no work presents a complete background of the field of study. This review is the first bibliometric performance and network analysis (BPNA) performed in the field of WOP.…”
Section: Introductionmentioning
confidence: 99%
“…We chose this journal for two reasons: First, previous estimates of publication bias detection in this journal have been consistent with the overall estimates of bias detection rates in this field (i.e., 31%;Kepes et al, 2012). Second, the Journal of Applied Psychology does not only publish the highest share of meta-analyses among top-tier journals in I/O Psychology (Aytug et al, 2012;Schalken & Rietbergen, 2017), but it has also been found to be more transparent in several aspects of meta-analytic reporting standards and to publish meta-analyses that are cited at a significantly higher rate (Aytug et al, 2012). Therefore, we were able to gather a large sample that consists of meta-analyses that conform to often-recommended meta-analytic standards (as evidenced by the high transparency scores) and represent valuable resources for researchers in the field (as evidenced by the high citation rates).…”
Section: Limitationsmentioning
confidence: 93%
“…For example, in the methodological study of Cochrane HIV systematic reviews, Mbuagbaw et al included all of the available studies ( n = 103) [ 30 ]. Methodological studies that include a sample of the target population Many methodological studies use random samples of the target population [ 33 , 91 , 92 ]. Alternatively, purposeful sampling may be used, limiting the sample to a subset of research-related reports published within a certain time period, or in journals with a certain ranking or on a topic.…”
Section: Main Textmentioning
confidence: 99%
“…Many methodological studies use random samples of the target population [ 33 , 91 , 92 ]. Alternatively, purposeful sampling may be used, limiting the sample to a subset of research-related reports published within a certain time period, or in journals with a certain ranking or on a topic.…”
Section: Main Textmentioning
confidence: 99%